Financial Governance and Management Strategies in Startup Ecosystems: A Bibliometric Analysis of Research Trends and Collaboration Networks - Ratna Dewi; Asriani Asriani; Yulinda L Ismail; Irawati Irawati; Firman Firman; Muh. Rezky (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
This study explores the intellectual development of research on financial governance and management strategies within startup ecosystems through a bibliometric analysis of Scopus-indexed publications from 2019 to 2025. Using VOSviewer, this study maps citation networks, co-authorship collaborations, keyword co-occurrence, and thematic evolution to identify dominant research patterns and emerging financial topics. The results reveal a significant growth in scholarly attention to financial management issues, including funding strategies, financial sustainability, governance mechanisms, and resource allocation in startup ecosystems. Network visualization identifies three major research clusters focusing on financial governance frameworks, strategic financial management and investment decisions, and sustainability-oriented financial practices. Overlay visualization indicates a temporal shift from early studies emphasizing startup financing and growth models (2019 - 2021) toward more recent themes such as financial resilience, sustainable finance, and digitally enabled financial management (2022-2025). Density visualization further highlights the concentration of influential contributions from developed economies, alongside increasing research participation from emerging and developing regions. Overall, this study offers a comprehensive mapping of the financial knowledge structure within startup ecosystem research and provides valuable theoretical insights and managerial implications for scholars, policymakers, and practitioners.